Lack of unique neuropathology in amyotrophic lateral sclerosis associated with p.K54E angiogenin (ANG) mutation. Issue 5 (9th July 2013) - Kirby, J.; Highley, J. R.; Cox, L.; Goodall, E. F.; Hewitt, C.; Hartley, J. A.; Hollinger, H. C.; Fox, M.; Ince, P. G.; McDermott, C. J.; Shaw, P. J.
<x xml:space="preserve">Abstract</x> Aims Five to 10% of cases of amyotrophic lateral sclerosis are familial, with the most common genetic causes being mutations in the C9ORF72, SOD1, TARDBP and FUS genes. Mutations in the angiogenin gene, ANG, have been identified in both familial and sporadic patients in several populations within Europe and North America. The aim of this study was to establish the incidence of ANG mutations in a large cohort of 517 patients from Northern England and establish the neuropathology associated with these cases. Methods The single exon ANG gene was amplified, sequenced and analysed for mutations. Pathological examination of brain, spinal cord and skeletal muscle included conventional histology and immunohistochemistry. Results Mutation screening identified a single sporadic amyotrophic lateral sclerosis case with a p.K54E mutation, which is absent from 278 neurologically normal control samples. The clinical presentation was of limb onset amyotrophic lateral sclerosis, with rapid disease progression and no evidence of cognitive impairment. Neuropathological examination established the presence of characteristic ubiquitinated and TDP‐43‐positive neuronal and glial inclusions, but no abnormality in the distribution of angiogenin protein. Discussion There is only one previous report describing the neuropathology in a single case with a p.K17I ANG mutation which highlighted the presence of eosinophilic neuronal intranuclear inclusions in the hippocampus. The absence of this feature in the present case indicates that patients with ANG mutations do not always have pathological changes distinguishable from those of sporadic amyotrophic lateral sclerosis.